Cell Transplantation and Neuroengineering Approach for Spinal Cord Injury Treatment: A Summary of Current Laboratory Findings and Review of Literature. Issue 8 (August 2016) - Lin, Xin-Yi; Lai, Bi-Qin; Zeng, Xiang; Che, Ming-Tian; Ling, Eng-Ang; Wu, Wutian; Zeng, Yuan-Shan
Spinal cord injury (SCI) can cause severe traumatic injury to the central nervous system (CNS). Current therapeutic effects achieved for SCI in clinical medicine show that there is still a long way to go to reach the desired goal of full or significant functional recovery. In basic medical research, however, cell transplantation, gene therapy, application of cytokines, and biomaterial scaffolds have been widely used and investigated as treatments for SCI. All of these strategies when used separately would help rebuild, to some extent, the neural circuits in the lesion area of the spinal cord. In light of this, it is generally accepted that a combined treatment may be a more effective strategy. This review focuses primarily on our recent series of work on transplantation of Schwann cells and adult stem cells, and transplantation of stem cell-derived neural network scaffolds with functional synapses. Arising from this, an artificial neural network (an exogenous neuronal relay) has been designed and fabricated by us—a biomaterial scaffold implanted with Schwann cells modified by the neurotrophin-3 (NT-3) gene and adult stem cells modified with the TrkC (receptor of NT-3) gene. More importantly, experimental evidence suggests that the novel artificial network can integrate with the host tissue and serve as an exogenous neuronal relay for signal transfer and functional improvement of SCI.